STEROIDAL SAPOGENINS 169 MAGOGENIN AND CACOGENIN AND THEIR BIOGENESIS TOCHLOROGENIN AND TIGOGENIN - MARKER, RE (HOTEL GENOVA, CD. MEXICO, DF, MEX, 1947)
Cacogenin and magogenin, two new steroidal sapogenins, have been isolated from the young plants of Maguey cacaya and their structures determined. Old plants gave manogenin, gitogenin, chlorogenin and tigogenin.
J OPT SOC AM
Keywords: STEROIDAL SAPOGENINS. 169., MAGOGENIN, CACOGENIN, BIOGENESIS TOCHLOROGENIN, TIGOGENIN; QUIMICA; QUIMICA FISICA; QUIMICA AMBIENTAL